Transaction Agreements Through Internet Media Electronic Systems (E-Commerce) in the Perspective of Civil Law and Islamic Law - Dewi Arnita Sari (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
E-Commerce or what is known as electronic commerce is a product in the digital era. E-Commerce Agreements have become a new color in the economic world, especially in providing convenience in making an agreement in a transaction. Like an agreement in general, but the difference is that the contract is not in one assembly. It is urgent to get a factual answer related to its validity in the dimensions of civil law and Islamic law. nik. This study is normative research with literature study. The results of this study indicate that: (1) Even though there is one of the legal conditions of the agreement that is not fulfilled, namely the qualification requirements of the parties, the agreement made by the merchant and customer remains valid and binding and becomes a law for merchants and customers because the skill requirements are included in subjective conditions where a condition is not fulfilled in the agreement. does not cause the agreement or contract to be invalid, but the agreement or contract can be requested for cancellation. Meanwhile, according to the Islamic perspective, it is permissible as long as it does not contain elements that can damage it, such as tyranny, fraud, cheating, containing usury, forbidden cases and the like and fulfilling the pillars and conditions of buying and selling. (2) Then, problems in the implementation of E-Commerce can actually be overcome by using technology assistance, including cryptography and digital signatures that are useful for providing guarantees of data authenticity, data confidentiality, and data validity using SSL (Secure Socket Layer) on the browser engine to provide security against eavesdropping. data in the process of electronic transactions. Cooperation between merchants and banks and account and credit card issuers to ensure the accuracy of the data submitted, especially regarding skills. Good faith from the merchant by using software that has been tested to always update the information submitted in order to provide correct information about the existence of the goods.